2017
DOI: 10.1111/jocn.13732
|View full text |Cite
|
Sign up to set email alerts
|

Medication administration errors and related deviations from safe practice: an observational study

Abstract: Factors associated with wrong-time errors and omissions should be addressed. Patient identification and asepsis protocols should be adhered to. Dosage calculation training is indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 37 publications
3
37
1
4
Order By: Relevance
“…The wrong time error finding was the most prevalent during observation of nurses administering medications in the current study. This finding compares closely with most MAEs studies done in similar settings including Alemu, Belachew & Yimam (2017), who reported that failure to administer medications at the right time was the second most commonly perpetrated incident [26], while a similar study in south Africa found that the most common types of errors were wrong-time errors at 43% and errors of omission at 41%, followed by wrong-dose errors 12% [10].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The wrong time error finding was the most prevalent during observation of nurses administering medications in the current study. This finding compares closely with most MAEs studies done in similar settings including Alemu, Belachew & Yimam (2017), who reported that failure to administer medications at the right time was the second most commonly perpetrated incident [26], while a similar study in south Africa found that the most common types of errors were wrong-time errors at 43% and errors of omission at 41%, followed by wrong-dose errors 12% [10].…”
Section: Discussionsupporting
confidence: 85%
“…Tool 2: Nurses' medication administration errors observation checklist, was developed by the researchers after thorough review of related literature [5,10,[16][17][18][19][20][21]. The tool aimed to observe medication administration errors committed during the medication administration process by nurses in the medical and surgical units of the hospital.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…No studies were identified that specifically reported transcribing errors, dispensing errors and medication history errors. Most studies (12/36) were conducted in Nigeria and 8 studies [ 55 , 60 , 62 , 67 69 , 74 , 78 ] were conducted in a multicentre setting. Five studies [ 50 , 52 , 56 , 65 , 79 ] were solely conducted in a paediatric ward and one study [ 73 ] in an obstetric ward.…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies [ 57 59 , 61 , 62 , 65 , 66 , 68 ] calculated medication administration error rate. A study by Amucheazi and Ajuzieogu [ 61 ] analysed only a single component of the medication administration procedure in an anaesthetic department, with incorrect drug administration reported in 0.5% of elective surgical procedures.…”
Section: Resultsmentioning
confidence: 99%